MANIFESTATIONS OF PEACE, LOVE AND TOLERANCE IN PAKISTANI LITERATURE: IN THE CONTEXT OF CONTEMPORARY SITUATION - Kamran, Muhammad (PUPIL: International Journal of Teaching, Education and Learning, 2024)
If we review the history of Asian literature, the literature created in Pakistan's national language, Urdu, is generally a message of love, peace, tolerance and coexistence. Pakistan's national poet Allama Muhammad Iqbal has declared love as the conqueror of the world in his poetry. The main message of mysticism and knowledge poetry in the regional languages ​​of Pakistan is love and tolerance. The revolutionary poetry of Pakistan's prominent poet Faiz Ahmed Faiz, which is the bearer of positive change in society, calls love and freedom of expression as fundamental human values. Ahmed Nadeem Qasmi in his poetry awakens the consciousness to end the sufferings and deprivations of the common man. Munir Niazi and Ahmed Faraz raise their voices for the creation of an enlightened and moderate society. Amjad Islam Amjad describes love as the most beautiful dream of the human eye. Overall, the main theme of Pakistani poems and ghazals is love and philanthropy. This poetry refutes the general impression of the West, under the influence of which terrorism and intolerance are linked to Pakistani society. In this paper, along with Pakistani literature, the social and cultural landscape of South Asia will also be highlighted.